Global health inequities in retinoblastoma: a 1990–2021 analysis across socio-demographic index regions - Xi Li; Ying Chang; Xiaoyu Zhao; Xi Liu; Ying Zhang; Xuan Wang; Junhong Li (Frontiers in Public Health)
ObjectiveTo assess health inequities associated with retinoblastoma across various Socio-Demographic Index (SDI) regions and evaluate whether these inequities have decreased from 1990 to 2021, with the aim of enhancing awareness and guiding government policies.DesignPopulation-based demographic analysis.ParticipantsChildren diagnosed with retinoblastoma from 204 countries and territories.MethodsThe estimates and their 95% uncertainty interval (UI) for disability-adjusted life-years (DALYs) of retinoblastoma were extracted from Global Burden of Disease study (GBD) 2021. The age-standardized DALYs and the average annual percentage change (AAPC) were evaluated.Main measuresThe Slope Index of Inequality (SII) and concentration index were computed to quantify the absolute and relative cross-national health inequality.ResultsAll SDI regions and the majority of countries experienced a significant decline in age-standardized DALYs from 1990 to 2021. The decrease was more rapid in middle to high SDI regions than in low to low-middle SDI regions. Globally, the 2–4 years age group had the highest DALYs rate, consistent with trends in low to middle SDI regions. In contrast, the highest DALYs rate in high and high-middle SDI regions was found in the 12–23 months age group. The SII was −40.81 (95% CI −36.04 to −45.58) DALYs per 100,000 population in 1990 and − 30.32 (95% CI −27.18 to −33.47) DALYs per 100,000 population in 2021. The concentration index increased from −0.37 (95% CI −0.46 to −0.28) in 1990 to −0.45 (95% CI −0.53 to −0.36) in 2021, although this increase did not reach statistical significance (p = 0.256).ConclusionDespite advancements in retinoblastoma management, the overall burden of the disease-related DALY remains disproportionately concentrated in poorer populations. The health inequalities are persisting and widening. This underscores the limitations of current efforts. Until progress benefits everyone, the vision of equitable healthcare remains imperfect.